Underground Coal Mining: Relationship between Coal Dust Levels and Pneumoconiosis, in Two Regions of Colombia, 2014. (20th August 2015) - Torres Rey, Carlos Humberto; Ibañez Pinilla, Milciades; Briceño Ayala, Leonardo; Checa Guerrero, Diana Milena; Morgan Torres, Gloria; Groot de Restrepo, Helena; Varona Uribe, Marcela
Abstract : In Colombia, coal miner pneumoconiosis is considered a public health problem due to its irreversibility, high cost on diagnosis, and lack of data related to its prevalence in the country. Therefore, a cross-sectional study was carried out in order to determine the prevalence of pneumoconiosis in underground coal mining workers in two regions of Colombia. The results showed a 35.9% prevalence of pneumoconiosis in the study group (42.3% in region 1 and 29.9% in region 2). An association was found between a radiologic diagnosis of pneumoconiosis and a medium risk level of exposure to carbon dust (OR: 2.901, 95% CI: 0.937, 8.982), medium size companies (OR: 2.301, 95% CI: 1.260–4.201), length of mining work greater than 25 years (OR: 3.222, 95% CI: 1.806–5.748), and a history of smoking for more than one year (OR: 1.479, 95% CI: 0.938–2.334). These results establish the need to generate an intervention strategy aimed at preventing the identified factors, as well as a timely identification and effective treatment of pneumoconiosis in coal miners, in which the commitment of the General Health and Social Security System and the workers compensation system is ensured.